The emergence of nominal expressions in Spanish-English early bilinguals : economy and bilingual first language acquisition - Ticio, M. Emma (Studies in bilingualism, 2018)
"This monograph examines the first syntactic unit in child language by presenting a longitudinal multiple-case study that focuses on the inner structure of nominal expressions in bilingual or monolingual child Spanish. This compilation of case studies offers the first insight on some of the properties of nominal expressions in bilingual or monolingual child Spanish and test some of the current theoretical proposals to analyze the main syntactic properties and operations within the nominal phrase. The findings of the study suggest new directions to address some core questions about monolingual and bilingual language acquisition taking as a point of departure the notion of economy, prevalent in the most recent theoretical discussion. Given the combination of empirical and theoretical discussions, this monograph will be appealing to a broad range of researchers in syntax and language acquisition"--